La literatura infantil y su incidencia en el desarrollo de destrezas de comprensión y expresión oral de los niños y niñas de primer año de educación básica del instituto educativo “Ludoteca” de la ciudad de Quito. Período lectivo 2013-2014”. Lineamientos alternativos - Celorio Lozada, Carina Mireya (2014)
This thesis entitled " THE CHILDREN'S LITERATURE AND ITS IMPACT ON THE DEVELOPMENT OF SKILLS SPEAKING OF UNDERSTANDING AND CHILDREN FIRST YEAR BASIC EDUCATION EDUCATIONAL INSTITUTE " LUDOTECA "DE QUITO . LECTIVO PERIOD 2013-2014 " . ALTERNATIVE GUIDELINES , is structured and developed in accordance with the Rules of Academic Board of the National University of Loja. Elobjetivo general who led the research was: To meet the educational community importance of Children's Literature in the Development of Skills and Speaking of children of First Grade Students Education “Playroom " Educational Institute Quito . 2013-2014 school. The methods used for the preparation of this research work were : Scientist, Inductive- Deductive , Analytic - Synthetic , Descriptive and Statistical Model that served them help effectively achieve the proposed goal. The techniques used were: a survey of teachers in First Year of Basic Education " playroom " of Quito Educational Institute to establish the type of children's literature that used in Everyday Workday and applied Observing Guide children children from First Year of Basic Education " Playroom " Educational Institute of the city of Quito, to determine the development of skills and Speaking . App Survey the teachers concluded that : 100% of the teachers surveyed used the following types of Children's Literature in the daily work as folk tales , fables , rhymes , riddles and tongue twisters and 50 % classic tales . Since they are teaching resources that are specific to stimulate children to develop skills and Speaking characteristics. According to the results of the Observation Guide is concluded that: 51% of boys and girls have investigated Skills development and Speaking Very Satisfactory , 37% and 12% Satisfactory Unsatisfactory The and Speaking is a skill that students practice very often because it is a very important procedure for acquiring other instrumental learning.